Competence of the provincial superior of a religious institute in the field of material goods and their administration - STOKŁOSA, MAREK (Prawo Kanoniczne, 2017)
Each province of the religious institutes, as a legal person in the Church has the right to acquire, possess, administer and alienate their material goods. These acts are taken by the provincial superiors while maintaining the common law and of own institute. All activities related to the ordinary administration may be taken by those superiors, but respecting the roles and responsibilities of the Provincial Treasurers provided for by law in this regard. Hence, fulfilling the acts of ordinary administration of material goods we should avoid any conflict between the two offices. Between the superior and treasurer there should be a mutual trust and be kept a constant dialogue on the administration of the entrusted material goods. Any acts of extraordinary administration remain within the competence of the provincial superior, who in some cases provided by law, may/can delegate them to other members of the Institute, including treasurers. While the act of alienation of material goods can be taken by the provincial superior or general, depending on the value of alienated goods. If the value of the transaction exceeds the sum determined by the Holy See for the region, then the permission for the act of alienation shall be given by the Holy See.